A Mechanistic Approach Towards the Discovery of Catalytic Acylation Reactions - Zhang, Wanying (Université d'Ottawa / University of Ottawa, 2017)
The development of new, efficient methods for the formation of carbon-carbon bonds using transition metal catalysis has broad applications in the field of organic chemistry and is the key to efficient chemical synthesis. Many efforts had been made to develop efficient ways to make these linkages particularly with the aid of metals such as Rh, Pd, Ni, Ru and Cu. Our group is primarily focused on exploring how these transition metals can activate typically inert functional groups, paving way to new synthetic routes to construct more complex molecules. Chapter 1 describes attempts that were conducted to achieve hydroacylation between an aldehyde and a non-conjugated alkene via a metal hydride intermediate. The use of RuHCl(CO)(PPh3)3 proved to be the most efficient catalyst for this transformation thus far. Mechanistic investigations were conducted to explore different possibilities to enable this transformation. This chapter also identifies a new self-aldol domino reaction, which consists of a self-aldol condensation of an aldehyde, followed by oxidation and decarbonylation giving rise to a ketone product. Finally, the use of a simple and direct method to access deuterated aldehydes using RuHCl(CO)(PPh3)3 as a catalyst and D2O as a deuterium source is outlined. Chapter 2 describes a novel Suzuki-Miyaura system that couples esters and boronic esters to form the corresponding ketone product. It was found that an NHC-based Pd catalyst is crucial in the transformation wherein it activates the C(acyl)-O bond of the ester. It is notable that this transformation takes place with the absence of decarbonylation. Reactivity under water in the presence of surfactants was also discovered. Results in aqueous media were demonstrated to be milder than in organic conditions, while achieving similar yields. This system was also applied to coupling of esters and anilines.
Keywords: Organometallic chemistry; Catalyst; Acylation; Aldol; Suzuki; Coupling